Trans-versing Latin America: Networks, Labour and Sexuality - Lidia Raquel García Díaz (Íconos)
Sexuality, understood as a historical and political structure that configures norms and social laws that condition individual subjectivities, is a fundamental element in migration studies. Using a qualitative approach, this article analyses the trans-versing of the female transsexual experience in Ecuador at the local and regional level. The principal elements analysed include the role of sexuality in the establishment of migratory networks, modifications of the body and the insertion into the labour market for sex work. These elements inter-relate in the migratory experiences of the female transsexual population in Quito.